2009
DOI: 10.1111/j.1582-4934.2008.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase in normal human tissues – is COX‐1 really a constitutive isoform, and COX‐2 an inducible isoform?

Abstract: Cyclooxygenase (COX) is a key enzyme in prostanoid synthesis. It exists in two isoforms, COX-1 and COX-2. COX-1 is referred to as a ‘constitutive isoform’, and is considered to be expressed in most tissues under basal conditions. In contrast, COX-2 is referred to as an ‘inducible isoform’, which is believed to be undetectable in most normal tissues, but can be up-regulated during various conditions, many of them pathological. Even though the role of COX in homeostasis and disease in now well appreciated, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(161 citation statements)
references
References 57 publications
7
150
0
4
Order By: Relevance
“…Of interest is the presence of COX-1 protein in the proximal convoluted tubule, a finding that has not previously been reported. COX-1 expression was also evident within the endothelial cells of the renal vasculature and the cortical and medullary collecting ducts which agree with previous reports (Vitzthum et al, 2002;Zidar et al, 2008). Immunohistochemical analysis revealed COX-A c c e p t e d m a n u s c r i p t 9 1 staining within the parietal epithelium of the Bowman's capsule.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Of interest is the presence of COX-1 protein in the proximal convoluted tubule, a finding that has not previously been reported. COX-1 expression was also evident within the endothelial cells of the renal vasculature and the cortical and medullary collecting ducts which agree with previous reports (Vitzthum et al, 2002;Zidar et al, 2008). Immunohistochemical analysis revealed COX-A c c e p t e d m a n u s c r i p t 9 1 staining within the parietal epithelium of the Bowman's capsule.…”
Section: Discussionsupporting
confidence: 81%
“…Immunohistochemical analysis revealed COX-A c c e p t e d m a n u s c r i p t 9 1 staining within the parietal epithelium of the Bowman's capsule. This is in keeping with data from Zidar et al (2008) who localized COX-1 expression in the same area. However this study did not find COX-1 staining within the mesangium of the glomerulus.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although more highly variable, COX-2 protein was found in nearly all tissues and was most often localized to parenchymal cells (13). Constitutive COX-2 expression is well recognized in brain, kidney, and the female reproductive tract, and evidence for induction of COX-1 during the lipopolysaccharide (LPS)-mediated inflammatory response and cellular differentiation has been reported (14)(15)(16)(17)(18).…”
Section: Differential Expression Of Cox-1 and Cox-2mentioning
confidence: 99%
“…In the same context, it has been suggested that the anti-inflammatory actions of NSAIDs are induced by the inhibition of COX-2, while their adverse effects of ulceration are precipitated by the over-inhibition of COX-1. 3 Another contributing factor to gastric side effects of NSAIDs is their local action. NSAIDs are reported to remain in crystalline form in the acidic medium of the stomach.…”
Section: Introductionmentioning
confidence: 99%